A study on factors affecting the Head Stack Assembly (HSA) in ultra sonic tab bond process - Onpimai, Jeeraporn; Tangchaichit, Kiatfa (Asia-Pacific Journal of Science and Technology, 2017)
Ultrasonic tab bond (USTB) is one of the processes in head stack assembly (HSA) production. It consists of a welding technique using high frequency vibration applied to the actuator pivot flex assembly (APFA) pad and the head gimbals assembly (HGA) pad or trace being held together under pressure. The variables which are assumed to affect this process which are the force of the welding tip and the duration time of the ultrasonic vibration are analyzed in this research. The stress behavior during the USTB process was analyzed using the finite element method (FEM). The results show that the stress when the compression was between 50–80 gf, while the ultrasonic time was between 325– 425 ms had no effect on the USTB process.bb